The Impact of Financial Technology and MSMEs in Mataram City: Increasing Financial Literacy Based on Payment Gateways - Raharja, Lalu Bayu Segara Kusna; Lestari, Baiq Anggun Hilendri (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to analyze the Impact of Financial Technology and on MSMEs in Mataram City: Increasing Financial Literacy Based on Payment Gateway. This study uses primary data or data collected directly from MSME actors and the sample in this study, a total of 60 respondents were obtained. This study uses the Smart PLS 4.0 data analysis tool. The results of this study are that fintech adoption and transaction volume have a positive effect on financial literacy. This means that the better the adoption of fintech and transaction volume, the better the financial literacy of MSMEs in Mataram City. This study is limited to the use of fintech adoption and transaction volume variables so that for subsequent researchers it is necessary to develop other variables that are rarely or have never been studied before and also increase the number of respondents so that the results obtained are better.